Sleep Quality Is Related to Disease Activity in Patients With Ankylosing Spondylitis: A Polysomnographic Study - In, Erdal; Turgut, Teyfik; Gulkesen, Arif; Yolbas, Servet; Akgol, Gurkan; Koca, Suleyman Serdar (Lippincott Williams & Wilkins, 2016)
Background Ankylosing spondylitis (AS) is a chronic inflammatory disease that is associated with poor sleep quality. Objectives The present study aimed to investigate the relationship between disease activity and sleep quality in patients with AS and to evaluate the potential effect of anti-tumor necrosis factor (TNF) treatment on sleep quality and pattern. Methods Fifty-nine patients with AS were consecutively included in the study. Twenty-eight patients (47.5%) were receiving anti-TNF, and 31 (52.5%) patients were receiving only nonsteroidal anti-inflammatory drugs (NSAIDs). Demographic and treatment characteristics, spinal mobility measurements, disease activity measurements, and sleep questionnaire results of each patient were recorded. Each patient underwent a polysomnography examination for the evaluation of sleep patterns. Results When compared with the patients on NSAID treatment, patients receiving anti-TNF treatment had significantly greater total sleep time and sleep efficiency (P = 0.003 and P < 0.001, respectively). They had a significantly lower (better) Pittsburgh Sleep Quality Index, sleep onset latency, number of awakenings, and arousal index (P < 0.001, for all). Moreover, they had a significantly shorter superficial sleep period (stage 1) and a significantly longer rapid eye movement sleep period (P < 0.001 and P = 0.02, respectively). Higher indexes of disease activity (Bath AS Disease Activity Index, Bath AS Functional Index, and visual analog scale) were reflecting poorer sleep quality. Conclusions Sleep quality and pattern was markedly better in patients with AS on anti-TNF compared with the patients on NSAID treatments. Increased disease activity can impair the quality of sleep in AS. Improved sleep quality and pattern in patients on anti-TNF treatment may be related to improved disease activity.
Keywords: ankylosing spondylitis; sleep; polysomnography; anti-TNF treatment